Respon tanaman kedelai terhadap pemupukan kombinasi bio-slurry dengan pupuk nitrogen - Reza Mas Indrawan; Yafizham Yafizham; Sutarno Sutarno (Department of Agriculture, Animal and Agricultural Sciences, Diponegoro University, Semara, 2018)
The research aimed to study the effect of fertilizer combination of by bio-slurryand nitrogen on the growth and yield of soybean. The experiment was assigned in monofactor randomized block design with treatments of P0. Control (without fertilizer), P1. Bio-slurry 10 t/ha + 11,5 kg N/ha, P2. Bio-slurry 10 t/ha + 23 kg N/ha, P3. Bio-slurry 10 t/ha + 34,5 kg N/ha, P4. Bio-slurry 10 t/ha + 46 kg N/ha. P5. Bio-slurry 10 t/ha. Each treatment was replicated five times. Parameters measured were plant height, leaf number, number of pods/plot seed weight/plot, and nitrogen uptake of plant. Data were subjected to analysis of variance and followed by Duncan test. The result showed that combination of bioslurry and nitrogen increased growth and yield of soybean significantly (P<0,05). Bio-slurry+ 23 kg N/ha increased plant height (28.10 cm) and leave number (8.48 leaves) significantly higher than other treatments. Bio-slurry + 11.5 kg N/ha was non-significantly different from bio-slurry + 23 kg N/ha on number of pods/plot, although significantly higher than other treatments. Bio-slurry + 11,5 kg N/ha increased seed weight/plot (1853 g) significantly higher than other treatments. Nitrogen uptake of plant of 62,88 g/plant has resulted by bio-slurry + 11,5 kg N/ha which was higher than other treatments, but non-significantly different from bio-slurry + 23 kg N/ha (50,63 g/plant). Keyword : Bio-slurry, combination, growth, nitrogen, soybean, yield